2013
DOI: 10.1002/jgra.50451
|View full text |Cite
|
Sign up to set email alerts
|

The proton temperature anisotropy associated with bursty bulk flows in the magnetotail

Abstract: [1] We study the development of the proton temperature anisotropy T ⊥ /T || in bursty bulk flows (BBFs), as observed by THEMIS Mission. For a set of 10 selected events, during which at least three spacecraft are aligned in the same flow, we can sample the plasma parameters along the Earth's magnetotail. The temperature anisotropy in the quiescent tail is negligible. However, as soon as the BBF passes over the spacecraft a strong anisotropy is measured. We analyze T ⊥ /T || as a function of parallel plasma beta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 43 publications
(70 reference statements)
1
15
0
Order By: Relevance
“…The adiabatic betatron heating through the magnetic pileup process can also lead to the perpendicular heating in the near‐Earth magnetotail [ Wu et al ., ]. In our simulation, we find that adiabatic betatron heating can make a small contribution to account for the ion heating in the dipolarization region.…”
Section: Summary and Discussionmentioning
confidence: 62%
“…The adiabatic betatron heating through the magnetic pileup process can also lead to the perpendicular heating in the near‐Earth magnetotail [ Wu et al ., ]. In our simulation, we find that adiabatic betatron heating can make a small contribution to account for the ion heating in the dipolarization region.…”
Section: Summary and Discussionmentioning
confidence: 62%
“…In ∼ 300 s the plasma in the jet with a speed ∼ 700 km/s also moves ∼ 30 R E ∼ 200d i,exhaust downstream. The situation is probably different in near tail, where the exhaust is wider and magnetic field is stronger; recently, Wu et al [2013] reported more isotropic plasma in bursty bulk flows observed at X > −14 R E than at X < −14 R E . Speiser-like, meandering ion motion at the neutral plane of the reconnection exhaust has been reported in many hybrid [e.g., Nakamura et al, 1998;Lottermoser et al, 1998;Arzner and Scholer, 2001;Higashimori and Hoshino, 2012] and PIC [e.g., Drake et al, 2009;Zenitani et al, 2013] simulations and within the ion diffusion region [Nagai et al, 2015] and in a plasmoid event in the magnetotail [Hoshino et al, 1998].…”
Section: Discussionmentioning
confidence: 98%
“…In ∼300 s the plasma in the jet with a speed ∼700 km/s also moves ∼30 R E ∼200 d i ,exhaust downstream. The situation is probably different in near tail, where the exhaust is wider and magnetic field is stronger; recently, Wu et al [] reported more isotropic plasma in bursty bulk flows observed at X >− 14 R E than at X <− 14 R E .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These waves, which are continually radiated outward from the BBFs to the auroral oval, are found to be a very efficient plasma sheet energy loss process [ Chaston et al , ; Ergun et al , ], transferring the energy from the fields to the plasma [ Huang et al , ; Angelopoulos et al , ]. Whistlers have been previously recorded on board Cluster [ Khotyaintsev et al , ; Huang et al , ] and Time History of Events and Macroscale Interactions during Substorms (THEMIS) [ Le Contel et al , ; Deng et al , ] and are thought to be generated by the perpendicular electron temperature anisotropy resulting from betatron acceleration that occurs as the magnetic field strength increases inside the FPR [see, e.g., Wu et al , ; Fu et al , ; Huang et al , ; Wu et al , ]. Deng et al [] investigated the properties (namely, propagation angle, degree of polarization, and ellipticity) of whistler waves inside the magnetotail FPR, and by analyzing Poynting flux, Khotyaintsev et al [] have shown that these waves are generated near the geomagnetic equator.…”
Section: Introductionmentioning
confidence: 99%